El sentir del descanso contemplamos la herencia de la tierra (2023)
The project The Feeling of Rest is an Architectural proposal with which we seek the improvement and conservation of a lot that is under constant pressure from urban growth which lives thanks to its two neighbors. The Altamira farm currently has more than 30 hectares for its use, also counting on the protection ring that must be managed on the edge of the Tunjuelo River. Currently the farm is a producer of craft beer, dairy products, pollen, honey and its main income is a soccer field with the cafeteria. The project located on Carrera 14 with Calle 131 Sur has as a neighboring project the La Hacienda el Carmen Archaeological Park, which is our main partner when thinking about the project growth we are looking for. We know that the closest parking spaces are in Usme Pueblo and near the Usme Portal Urbanization, which is why the approach we seek to generate at Finca Altamira is to give up a space on our lot for Usme where the design of a new road can be made. to be able to have better circulation and in addition we will give a space for the proposal of a parking lot where it will not only be a tourist connector for our project but also give the opportunity to tourists from the archaeological park to find a place close to park and that they do not have to take a tour from Usme Pueblo to the Park. Seeking to make the tour more enjoyable and pleasant, we designed a bridge so that people can connect from the Finca Altamira project to the Hacienda el Carmen project.